Audiometric profile of traffic operators exposed to urban noise in the city of Sao Paulo, Brazil (Saúde Ética & Justiça, 2004)
The purpose of this study was to compare the audiometric profile of Traffic Operators who work in Sao Paulo´s urban areas presenting the highest and the lowest noise levels, 83,4 dB HL and 79 dBHL respectively, according literature data. In addition, the association between hearing loss and some others features (age, working time, nonoccupational exposure to noise, use of individual protection equipment and tinnitus complain) was verified. It was used data on 73 workers, previously submitted to hearing tests and a clinical questionnaire, obtained from the University of Sao Paulo’s Occupational Health Service database. The results suggest that non-occupational exposure to noise, but not occupational exposure, had an effect on hearing loss.